SOCIAL PRACTICES AS IMPLEMENTED FROM THE TEXTUAL ANALYSIS IN VANGUARD: SEX, LIES AND CIGARETTES DOCUMENTARY FILM - ALVIONITA, RINTA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Critical Discourse Analysis, Social Practice, Textual Analysis, Intertextuality This study is about the analysis of Vanguard: Sex, Lies and Cigarettes the documentary film by using Fairclough (1992) three dimensional models theory ofCDA. The first objective of this study is to describe the meaning constructions found in the textual analysis as uttered by the reporters and the interviewees in Vanguard: Sex, Lies and Cigarettes the documentary film, while the second one is to find out the aspects of social practice implemented from the the textual analysis in Vanguard: Sex, Lies and Cigarettes the documenary film.A qualitative method was used to analyze the data. The writer collected the data by transcribing all utterances produced by the reporter and four interviewees. The data is from 59 (fifty nine) utterances out of all utterances which contain the issue of Indonesian smoking children. In analyzing the data, the writer used textual analysis and social practice analysis from three dimensional models as proposed by Fairclough (1992).The textual analysis has been done to describe and to analyze the utterances by using five techniques of intertextuality in order to construct the meaning on it. Then, the textual analysis has confirmed to find out the aspects of social practice which is divided into two aspects: public discourse control and mind control.The result of this study confirmed that text, as the result of social structure and social interaction has emerged social practices. In line with linguistic features, textual analysis through techniques of intertextuality could implement the aspects of social practice toward the phenomenon of Indonesian smoking children as shown in Vanguard: Sex, Lies and Cigarettes the documenary film. Moreover, all aspects of social practice have equally big influence for attracting Indonesian children to smoke.  Finally, the writer suggested the next writer to apply and to elaborate more theoris of CDA, especially structural content for completing the textual analysis to understand the structure under such condition of certain text. Whereas the idelogies constructed through social practice also needs to be found for a complete and a better study.